ANTIOXIDANT ACTIVITY TEST OF JENGKOL LEAF EXTRACT (Archidendron pauciflorum (Benth.) I.C. Nielsen) USING DPPH (1,1-diphenyl-2-picrylhydrazyl) METHOD - Manurung, Aisyah Baddriah; Ridwanto (PT Inovasi Pratama Internasional, 2022)
Jengkol leaf (Archidendron Pauciflorum (Benth.) I.C.Nielsen) contains alkaloids, tannins, saponins, flavonoids, steroids/triterpenoids. The objective of this research was to determine the class of chemical compounds contained in simplisia and jengkol leaf extract as well as the antioxidant activity of jengkol leaf extract. The research stages include the collection and processing of simplicia, the manufacture of extracts by maceration with 96% ethanol solvent. Phytochemical screening of jengkol leaf powders and extracts includes examination of alkaloid compounds, tannins, saponins, flavonoids, and steroids. Examination of the characteristics of simplicia powder. The antioxidant and extract activity test of jengkol leaf extract was carried out using the DPPH method (1,1-diphenyl-2-picrilhydrazyl), where DPPH absorption was measured using a Vis spectrophotometer at a wavelength of 516 nm. The results of phytochemical screening, powders and simplician extracts contain alkaloid compounds, tannins, saponins, flavonoids, steroids / triterpenoids. The results of the examination of the characteristics of simplicia powder obtained a moisture content of 6.66%, a water-soluble juice content of 16.66%, an ethanol soluble juice content of 26.66%, a total ash content of 1.3%, an acid insoluble ash content of 0.42%. The results of measuring the antioxidant activity of jengkol leaf extract showed the strength of the